Assessing Self-Determined Work Motivation in People with Severe Mental Illness: A Factor-Analytic Approach. Issue 2 (17th November 2015) - Fitzgerald, Sandra; Chan, Fong; Deiches, Jon; Umucu, Emre; Hsu, Su-Ting; Lee, Hui-Ling; Bezyak, Jill; Iwanaga, Kanako
Abstract : B ackground : Self-determination theory (SDT) has increasingly been used as a theoretical framework for evaluating key elements of the recovery paradigm in rehabilitation and mental health services research and policy-making for people living with severe mental illnesses. Purpose : The purpose of this study was to validate the Behavioral Regulation in Work Questionnaire (BRWQ), an adaptation of the Behavioral Regulation in Exercise Questionnaire-2, as a measure of self-determined work motivation for use in psychiatric rehabilitation settings. Methods : One hundred and twenty-four individuals with severe mental illness were recruited from eight Clubhouse programmes in Hawaii. Factorial validity of the BRWQ was evaluated using exploratory factor analysis. Findings : Principal components analysis of the BRWQ yielded four factors (amotivation, external regulation, introjection and autonomous motivation). The autonomous motivation factor was found to be significantly related to other SDT constructs, including competency, relatedness, outcome expectancy and vocational rehabilitation engagement. Conclusions : The BRWQ is a psychometrically sound SDT measure for assessing self-determined work motivation and could contribute to the use of self-determination as a paradigm for improving recovery and employment outcomes of people with severe mental illness in rehabilitation settings.